Regulation of Th1/Th2 balance through OX40/OX40L signalling by glycyrrhizic acid in a murine model of asthma. Issue 1 (15th October 2015) - Wu, Qiaozhen; Tang, Ying; Hu, Xiaoyun; Wang, Qin; Lei, Wei; Zhou, Linfu; Huang, Jianan
Abstract: Background and objective: Glycyrrhizic acid (GA) has been reported to have attenuating airway inflammation effects in asthma mouse model. However, the potential molecular mechanisms by which GA exerts anti‐inflammatory effects on ovalbumin (OVA)‐induced allergic asthma have not been well elaborated. Methods: The effect of GA on OVA‐sensitized and challenged mice was investigated. The effect of GA on anti‐OX40 mAb stimulated splenocytes from asthma mice model was also examined. Results: In OVA‐induced asthmatic mice, GA treatment prevented the decrease of T helper1 cytokine (interferon (IFN)‐γ) and the increase of T helper2 cytokines (interleukin (IL)‐4, IL‐5, IL‐13) in bronchoalveolar lavage fluid (BALF), reduced serum immunoglobulin (Ig)E and OVA‐specific IgE levels, prohibited the protein and mRNA expression of OX40 and OX40 Ligand (OX40L) in lung tissues, and the expression of OX40 in CD4 + T cells and OX40L in CD11b + monocytes and CD19 + B cells in spleens in a dose‐dependent manner compared with the vehicle treatment (all P  < 0.05). Moreover, OVA significantly increased the activation of p38 mitogen‐activated protein kinase (MAPK) in lung tissues, whereas GA and anti‐OX40L mAb markedly reduced phosphorylation of p38 MAPK. In addition, GA could inhibit the T cell proliferation and modulate the balance of Th1/Th2 in anti‐OX40 mAb stimulated CD4 + T cells from asthmatic spleens (all P  < 0.05). Conclusions: GA may exert a therapeutic effect on OVA‐induced experimental asthma partly by regulating the Th1/Th2 balance through suppressing OX40‐OX40L signalling and p38 MAPK activity. GA may be a promising treatment for asthma. Abstract : We investigated the effect of glycyrrhizic acid (GA) on an OVA‐challenged model of asthma. GA‐modulated Th2 and Th1 reduced OX40, OX40L and p‐p38 MAPK in OVA‐challenged asthma mice model. GA also suppressed OVA‐induced and anti‐OX40 mAb stimulated splenocyte proliferation and Th2 production. GA has potential as a treatment for asthma.